The Role of Steroid Hormones in the Modulation of Neuroinflammation by Dietary Interventions - Vasconcelos, Andrea Rodrigues; Cabral-Costa, João Victor; Mazucanti, Caio Henrique; Scavone, Cristoforo; Kawamoto, Elisa Mitiko (Frontiers in Endocrinology, 2016)
Steroid hormones, such as sex hormones and glucocorticoids, have been demonstrated to play a role in different cellular processes in the central nervous system, ranging from neurodevelopment to neurodegeneration. Environmental factors, such as calorie intake or fasting frequency, may also impact on such processes, indicating the importance of external factors in the development and preservation of a healthy brain. The hypothalamic-pituitary-adrenal axis and glucocorticoid activity play a role in neurodegenerative processes, including in disorders such as in Alzheimer´s and Parkinson´s diseases. Sex hormones have also been shown to modulate cognitive functioning. Inflammation is a common feature in neurodegenerative disorders, and sex hormones/glucocorticoids can act to regulate inflammatory processes. Intermittent fasting can protect the brain against cognitive decline that is induced by an inflammatory stimulus. On the other hand, obesity increases susceptibility to inflammation, whilst metabolic syndromes, like diabetes, are associated with neurodegeneration. Consequently, given that gonadal and/or adrenal steroids may significantly impact on the pathophysiology of neurodegeneration, via their effect on inflammatory processes, this review focuses on how environmental factors, like calorie intake and intermittent fasting, acting through their modulation of steroid hormones, impact on inflammation that contributes to cognitive and neurodegenerative processes.